Determining Factors of the Intention to Adopt Fintech Services by Micro and Small Business Owners from Chiclayo, Peru (Journal of Business, Universidad del Pacífico (Lima, Peru), 2022)
The objective of this research was to determine the factors that influence the intention to adopt fintech services by micro and small business owners from Chiclayo; for this purpose, an applied quantitative study was carried out in which the extended technology acceptance model proposed by Hu, Ding, Li, Chen and Yang (2019) was used for the analysis of nine variables related to the adoption of these technologies. The results reaffirmed that most of the constructs included in the conceptual model have great explanatory power regarding the adoption intention of fintech services, in that 11 of the 13 hypotheses were proven. Thus, it was demonstrated that business owners from Chiclayo use a new technology mainly under the influence of factors such as trust, brand image, and perceived utility, while also considering the potential risks to which they may be exposed; together, these considerations influence  their attitude toward adopting fintech services. Finally, the analysis showed that government support and perceived ease of use have only a limited effect, while user innovativeness was the only factor that turned out to be non-significant in the intention to adopt this kind of services.
Keywords: Fintech; adoption intention; micro and small enterprises; Fintech services